Shortwave Diathermy Machine - Tamboli Simran; Mali Rutuja; Patil Supriya (Journal of Electronic Design Engineering, 2018)
In this paper, Diathermy is a most generally prescribed for muscle and joint conditions. It uses a high-frequency electric contemporary to stimulate warmth technology inside frame tissues. Shortwave diathermy makes use of excessive frequency electromagnetic power to generate heat. Diathermy uses high-frequency electric present day to supply warmth deep inner a centered tissue. it can attain regions as deep as two inches underneath the skins surface.